The top 100 most-cited articles on adult spinal deformity: The most popular topics are still sagittal plane parameters and complications - Liu, Fu-Sheng; Deng, Lin-Xia; Liu, Fu-Bing; Zhang, Qian-Shi; Wang, Xiao-Bin; Li, Jing (Frontiers in Surgery, 2023)
Purpose This study aimed to summarize the characteristics of the 100 most-cited articles on adult spinal deformity (ASD) and to analyze past and current research hotspots and trends. Methods Literature searches (from inception to 28 April 2022) using Web of Science databases were conducted to identify ASD-related articles. The top 100 most-cited articles were collected for further analysis. Meanwhile, author keywords from articles published in the last 5 years were selected for further analysis. Results The top 100 most-cited articles on ASD were selected from 3,354 papers. The publication year ranged from 1979 to 2017, and all papers were written in English. The citation count among them ranged from 100 to 1,145, and the mean citation number was 215.2. The foremost productive first author was Schwab F. University of Washington had the largest number of publications. The United States of America had the largest number of published articles (n = 84) in this field. Spine was the most popular journal. Complications were the most studied themes. The visualization analysis of author keywords from the literature in the recent 5 years showed that complications, sagittal plane parameters, and surgical techniques are still the research hotspots, and minimally invasive surgery will continue to develop rapidly. Conclusion Based on a comparative analysis of the results of bibliometric and visualization, complications and sagittal plane parameters are still the major topics of research at present and even later, and minimally invasive surgery has a growth trend in this field of ASD.